2010
DOI: 10.1007/s00277-010-1001-6
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplant outcomes are not affected by body mass index (BMI) in patients with haematological malignancies

Abstract: myelodysplasia, 7 T cell non Hodgkin's lymphoma 6 aplastic leukaemia and 7 myelofibrosis At transplantation 40% (N=133) patients had normal and 60%(N=198) high BMI with 14% of patients being obese (BMI>30). After a median follow-up of 24 months (range:2-79), the mean overall survival(OS) in patients undergoing allograft with normal BMI was 31 months as compared to 39 with high BMI ( p:0.06). The mean progression free survival(PFS) in patients undergoing allograft with normal BMI was 33 months as compared to 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 15 publications
2
38
0
1
Order By: Relevance
“…Given the hypermetabolic state patients endure due to stress placed on the body during transplant, nutrition can be an important factor in patient outcomes and a patient's BMI can help determine nutritional status before transplant. [18][19][20][21] The improved 100-day mortality in the obese group could be attributed to nutritional reserves that prevented malnutrition during the transplant process. Pretransplant assessment of performance status and comorbidities is an important aspect in determining a patient's ability to tolerate SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Given the hypermetabolic state patients endure due to stress placed on the body during transplant, nutrition can be an important factor in patient outcomes and a patient's BMI can help determine nutritional status before transplant. [18][19][20][21] The improved 100-day mortality in the obese group could be attributed to nutritional reserves that prevented malnutrition during the transplant process. Pretransplant assessment of performance status and comorbidities is an important aspect in determining a patient's ability to tolerate SCT.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Furthermore, under-and overweight patients are at an increased risk for complications, non-relapse mortality and overall survival after alloHCT. [7][8][9][10] To date, few studies have assessed nutritional status before alloHCT, and most of them only recorded body mass index (BMI) as a potential risk factor for survival. [7][8][9][10] Except for one report by Kyle et al 11 on the development of lean body mass, there were until now no longitudinal data on nutritional status and body composition in the early post-transplant period, although several reports showed that depletion of micronutrients, mainly vitamin D, is common before and after alloHCT.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] To date, few studies have assessed nutritional status before alloHCT, and most of them only recorded body mass index (BMI) as a potential risk factor for survival. [7][8][9][10] Except for one report by Kyle et al 11 on the development of lean body mass, there were until now no longitudinal data on nutritional status and body composition in the early post-transplant period, although several reports showed that depletion of micronutrients, mainly vitamin D, is common before and after alloHCT. [12][13][14] There are now many nutritional parameters available and validated for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…93 Third, with the increased use of umbilical cord blood transplantation, achieving an adequate stem cell dose for obese patients remains a challenge. 94 Although there are conflicting data surrounding the independent influence of obesity on allogeneic transplantation outcomes, [95][96][97] retrospective studies in this area are limited to some degree by selection bias and likely underestimate an adverse effect of obesity on outcomes. Overall, it is likely that obesity will limit the application of allogeneic transplant, should the use of this treatment modality become routine in patients with myeloma.…”
Section: Impact Of Obesity On Myeloma Treatment and Prognosismentioning
confidence: 99%